Assessment of Risk Factors for Gestational Diabetes Mellitus - Rabia Arshad; Nasim Karim; Muhammad Omar Shamim (ziauddin University, 2024)
Background: Gestational diabetes is a condition due to glucose intolerance that occurs in the few of the mothers during gestation. The pathophysiology originates as a result of increased placental hormones which have strong diabetogenic effect. It is strongly associated with multiple problems in mother and the baby and can even leads to unexplained fetal deaths in the end trimesters. So it is important to diagnose and treat females who are at greater risk than the others for developing gestational diabetes mellitus. Objective: To access the high risk factors associated with the development of gestational diabetes mellitus in 75 GDM diagnosed females Methods: After screening and diagnoses 75 GDM patients (Diabetic, Group B) and 25 normal healthy patients (Control, Group A) in Lyari General and Mamji Hospital were enrolled in the study. Their detailed history was taken regarding occupation, parity, history of abortions, still births, preterm births and family history of diabetes. Parameters including age, weight, fasting and random blood sugar level and glycated hemoglobin were recorded in a predesigned data form. The results were evaluated using SPSS 16. Results: Statistically significant difference was found between the mothers of diabetic and normal control group as regards the weight, age (p-value=0.01 and p=0.03) and family history of diabetes (p-value=0.00). Non-significant differences were found in the maternal occupation, parity, abortions, still births and pre-term births between the two groups Conclusion: Advance maternal age, weight and familial association of diabetes are the risk factors associated with the development of gestational diabetes. KEY WORDS: Diabetes, Gestational, Risk Factors, Glucose intolerance, Pregnancy trimester